Temperature dependence on the pesticide sampling rate of polar organic chemical integrative samplers (POCIS). Issue 10 (2nd October 2016) - Yabuki, Yoshinori; Nagai, Takashi; Inao, Keiya; Ono, Junko; Aiko, Nobuyuki; Ohtsuka, Nobutoshi; Tanaka, Hitoshi; Tanimori, Shinji
Abstract: Laboratory experiments were performed to determine the sampling rates of pesticides for the polar organic chemical integrative samplers (POCIS) used in Japan. The concentrations of pesticides in aquatic environments were estimated from the accumulated amounts of pesticide on POCIS, and the effect of water temperature on the pesticide sampling rates was evaluated. The sampling rates of 48 pesticides at 18, 24, and 30 °C were obtained, and this study confirmed that increasing trend of sampling rates was resulted with increasing water temperature for many pesticides. Graphic abstract: : Laboratory experiments were performed to determine the sampling rates of pesticides used in Japan. The sampling rates of 48 pesticides at 18, 24, and 30 °C were obtained, and these temperature dependences were confirmed.